Hubungan Homesickness Dengan Motivasi Belajar Pada Siswa Asrama Tahun Pertama MAN 2 Padang Panjang - Fisdeta, Farid; Guspa, Anindra (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Learning motivation is the drive that brings someone to carry out learning activities. Learning motivation is very important for students to be able to carry out their learning activities at school. New boarding students must stay in the dormitory during the educational process, while students are in the dormitory several things are inevitable, one of them is homesickness, which is a feeling of sadness that arises due to homesickness. The phenomenon of homesickness is thought to have a negative relationship with student learning motivation. This study was conducted using a quantitative correlation method to determine the relationship of learning motivation variables with homesickness. The sampling technique used simple random sampling technique with a sample of 147 dormitory students from 202 total population. The learning motivation instrument used is the MSLQ instrument by Pintrich & De Groot (1990) which has been adapted by the author (r 0.852) and the Homesickness instrument uses the HQ instrument (r 0.811) which has been adapted by Oktavia Arlindie (2022) Data analysis using product moment correlation. The results found that there was a negative and significant relationship between the learning motivation variable and the homesickness variable p = 0.00 < 0.05 and r = -378. The conclusion is that there is a significant negative relationship with moderate strength between learning motivation and homesickness in boarding students. Keywords: Learning motivation, Homesickness, Boarding students.